A modulation reference compensation method to realize fully decoupled power control for modular multilevel converters - Wang, Jinyu (2020)
This paper proposes a modulation reference compensation method to completely eliminate the intercoupling between the output active and reactive powers of modular multilevel converters (MMCs). Different from the existing methods, it is realized not based on an accurate control model, but by directly amending the initial arm modulation references of MMCs. Therefore, the proposed method is essentially a compensation algorithm, which is extremely easy to implement in a microcontroller with low calculation burden. In addition, it does not need any additional closed-loop controllers or voltage/current sensors, which is very beneficial to practical projects. The proposed method finally realizes accurate and fully decoupled active and reactive power regulation, avoids overload operation and protection malfunction, and significantly improves the dynamic performance of MMCs. The effectiveness and accuracy of the proposed analysis and compensation method are carefully verified by both simulation and experimental results.